Lifespan Extension Via Dietary Restriction: Time to Reconsider the Evolutionary Mechanisms?. (8th July 2020) - Moatt, Joshua P.; Savola, Eevi; Regan, Jennifer C.; Nussey, Daniel H.; Walling, Craig A.
Abstract: Dietary restriction (DR) is the most consistent environmental manipulation to extend lifespan. Originally thought to be caused by a reduction in caloric intake, recent evidence suggests that macronutrient intake underpins the effect of DR. The prevailing evolutionary explanations for the DR response are conceptualized under the caloric restriction paradigm, necessitating reconsideration of how or whether these evolutionary explanations fit this macronutrient perspective. In the authors' opinion, none of the current evolutionary explanations of DR adequately explain the intricacies of observed results; instead a context‐dependent combination of these theories is suggested which is likely to reflect reality. In reviewing the field, it is proposed that the ability to track the destination of different macronutrients within the body will be key to establishing the relative roles of the competing theories. Understanding the evolution of the DR response and its ecological relevance is critical to understanding variation in DR responses and their relevance outside laboratory environments. Abstract : The evolutionary explanations for lifespan extension in response to dietary restriction are frequently applied to macronutrient manipulations but were not all conceived in this context. It is argued that none of these theories alone can explain the patterns observed, instead suggesting a context dependant combination of all three is more likely.